The Effect of Authoritarian Leadership Style, Work Motivation, and Discipline on Employee Loyalty: Pengaruh Gaya Kepemimpinan Otoriter, Motivasi Kerja, dan Kedisiplinan Terhadap Loyalitas Karyawan - Purnami, Charina Laras; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2023)
This research was conducted with the aim of knowing the influence of leadership styleauthoritarian, work motivation, and discipline partially and simultaneously to loyaltyemployees at PT. Jayaland Hills Rays. This study uses a quantitative approach with questionnaire data collectiondistributed to 185 respondents. Samples are taken based on o`ne of the techniquesnon-probability sampling , the type of which is purposive sampling. Technical analysis of the data using the test instrument statement on the questionnaire (test validity,and reliability), classical assumption test (normality, linearity, multicollinearity, autocorrelation and heteroscedasticity) and multiple linear regression (multiple correlation test, multiple determination test,partial test and simultaneous test). The results obtained from this study are that there is an influence of leadership styleauthoritarian, work motivation, and discipline partially and simultaneously to loyaltyemployees at PT. Jayaland Hills Ray.